Structural and energy differentiation of water in partially dehydrated cells of Saccharomyces cerevisiae as influenced by organic solvents - Turov, V. V.; Gun'ko, V. M.; Gorbyk, P. P.; Kerus', S. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2007)
The Influence of organic solvents on associative structures of intracellular water and free energy interaction of water with intracellular functionalities which form endocellular space of yeast cells Saccharomyces cerevisiae has been studied by 1H NMR spectroscopy with layer- by-layer freezing-out of bulk and bound water. Water in partially dehydrated cells exists in unusual slightly association state in which average part of hydrogen bounds in each molecule of water less than one.